Frequency of spondylolysis and chronic low back pain in young soccer players - Marcos Vaz De Lima; Aires Duarte Júnior; Pedro Baches Jorge; Flavio Fernandes Bryk; Robert Meves; Osmar Avanzi (Coluna/Columna, 2014)
Objective: To demonstrate the safety of soccer for adolescents in terms of chronic lesions of the lumbar spine, particularly spondylolysis. Methods: 54 young players underwent a pre-season assessment. The athletes were submitted to radiography of the lumbosacral spine. Players complaining of chronic low back pain were later submitted to more specific tests. Results: only 1 athlete (1.85 % of our sample) had complaints of chronic low back pain. In this case, the radiograph showed olisthesis grade I spondylolysis at the L5 level. Conclusion: Soccer proved to be a very safe sport in terms of the risk of developing chronic lesions of the lumbosacral spine. However, the actual incidence of spondylolysis in these athletes was not determined because only plain radiographs were used in this study.